Ex situ Conservation Effort through the Inventory of Plant Diversity in Mount Seblat, Bengkulu - Imawan Wahyu Hidayat; Ikhsan Noviady; Yati Nurlaeni (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Mount Seblat, as part a of Kerinci Seblat National Park (KSNP), is a pristine and natural mountain, particularly from disturbances and destructions by human activities. Nevertheless, the richness of biological resources especially plant diversity.in this area has not been more explored. The purpose of this study was to conduct an inventory of plant diversity and to determine the plant species composition. The inventory activities were conducted by plants collection along the ascent route. The results were then be maintained through ex situ conservation method in Cibodas Botanical Garden (CBG). The study was conducted by exploratory method, from Seblat Ulu Village (641 m asl) up to altitude of 1,037 m asl. There were 18 points of plant sample observation with an area of 5 x 5 square meters per point. Plant collection obtained 380 specimens. Five groups of most collected plants were Lauraceae (18 species), Rubiaceae (8 species), Anacardiaceae (6 species), Annonaceae (5 species), and Fagaceae (4 species). In order to enrich the plants collection as well as conduct the ex situ conservation effort, plants from Orchidaceae were also collected which resulted in 33 species. These results were an important initial inventory of plant diversity of Mount Seblat, considering that there was no record as well as very limited current information. When the environment disturbance tends to increase, this information may act as a reference and an initial database to develop plants conservation effort and strategy in the future.